1999
DOI: 10.1002/(sici)1096-8628(19991008)86:4<366::aid-ajmg11>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of hydroxymethylbilane synthase mutations causing acute intermittent porphyria: Evidence for an ancestral founder of the common G111R mutation

Abstract: Acute intermittent porphyria (AIP), the most common hepatic porphyria, results from the half-normal activity of hydroxymethylbilane synthase (HMB-synthase; EC 4.3.1.8), the third enzyme in the heme biosynthetic pathway. Because life-threatening acute neurologic attacks of this autosomal dominant disease are triggered by various ecogenic factors (e.g., certain drugs, hormones, alcohol, and starvation), efforts have been directed to identify and counsel presymptomatic heterozygotes in affected families to avoid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 45 publications
2
28
0
Order By: Relevance
“…Recently, this mutation has been documented as the first mutation in AIP associated with a founder effect in North America with the identified founding couple (Greene-Davis et al 1997). Such a founder effect has been well documented in variegate porphyria, the other form of acute porphyria (Dean 1971;Meissner et al 1996;Warnich et al 1996;Groenewald et al 1998), and has also been observed in other AIP patients (De Siervi et al 1999). The other mutation in Japan, reported by Morita et al (1995), is a single base substitution C-to-T in exon 8 of the gene, which was the same as a common mutation in the Netherlands (Gu et al 1994).…”
Section: Discussionmentioning
confidence: 81%
“…Recently, this mutation has been documented as the first mutation in AIP associated with a founder effect in North America with the identified founding couple (Greene-Davis et al 1997). Such a founder effect has been well documented in variegate porphyria, the other form of acute porphyria (Dean 1971;Meissner et al 1996;Warnich et al 1996;Groenewald et al 1998), and has also been observed in other AIP patients (De Siervi et al 1999). The other mutation in Japan, reported by Morita et al (1995), is a single base substitution C-to-T in exon 8 of the gene, which was the same as a common mutation in the Netherlands (Gu et al 1994).…”
Section: Discussionmentioning
confidence: 81%
“…It was also reported in Slavic (Rosipal et al, 1997), French , British (Whatley et al, 1999), Swedish (Andersson et al, 1995;and Floderus et al, 2002) and Polish patients . In Argentina, the G111R mutation was detected in 12 families (De Siervi et al, 1999) which seem Normal individuals showed one band whereas a heteroduplex was observed in asymptomatic gene carriers. (B).…”
Section: Discussionmentioning
confidence: 99%
“…This finding suggests that HMBS is very prone to mutations which are usually family specific, since in only a few cases has the same mutation been found in nonrelated AIP patients. For example, some populations may present the same mutation, as with the missense mutation R173W which occurs in nonrelated Scottish patients (Greene-Davis et al, 1997) and G111R detected in 12 Argentine families (De Siervi et al, 1999). This molecular variability requires gene investigation of the 15 exons by single-stranded conformational polymorphism (Kauppinen et al, 1995), denaturing gradient gel electrophoresis (Gu et al, 1994;Puy et al, 1997), chemical cleavage mismatch (Ong et al, 1998), heteroduplex (Schreiber et al, 1995) or high-resolution melting analysis (Ulbrichova-Douderova & Martasek, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In this PCR protocol two sets of primers were used to amplify the entire PBG-D gene (10 kb) in two fragments, one including the promoter region to intron 3 (4.5 kb) and the other from exon 2 to exon 15 (5.5 kb). 5 The products obtained were assayed on 1% agarose gels stained with ethidium bromide and puri®ed employing the QIAquick PCR puri®cation kit from QIAGEN, USA.…”
Section: Methodsmentioning
confidence: 99%
“…5 The cycle sequencing reaction (30 cycles) was performed with a denaturation step of 30 s at 958C, annealing 30 s at 608C and extension 60 s at 728C. The reaction was stopped by adding 4.5 mL of stop solution (95% formamide, 20 mmol/L EDTA, 0.05% bromophenol blue and 0.02% xylene cyanole) and, after a denaturation step of 3 min at 948C, samples were loaded in a 4% acrylamide solution (19:1) containing 7 mol/L urea gel preheated at about 508C, and was run at 80 W for different periods depending on both the gene region to be read and the primer used.…”
Section: Methodsmentioning
confidence: 99%